Turbo twenty-three - Evanovich, Janet (2016)
In the heart of Trenton, N.J., a killer is out to make sure someone gets his just desserts. Larry Virgil skipped out on his latest court date after he was arrested for hijacking an eighteen-wheeler full of premium bourbon. Fortunately for bounty hunter Stephanie Plum, Larry is just stupid enough to attempt almost the exact same crime again . Only this time he flees the scene, leaving behind a freezer truck loaded with Bogart ice cream and a dead body--frozen solid and covered in chocolate and chopped pecans. As fate would have it, Stephanie's mentor and occasional employer, Ranger, needs her to go undercover at the Bogart factory to find out who's putting their employees on ice and sabotaging the business. It's going to be hard for Stephanie to keep her hands off all that ice cream, and even harder for her to keep her hands off Ranger. It's also going to be hard to explain to Trenton's hottest cop, Joe Morelli, why she is spending late nights with Ranger, late nights with Lula and Randy Briggs--who are naked and afraid--and late nights keeping tabs on Grandma Mazur and her new fella. Stephanie Plum has a lot on her plate, but for a girl who claims to have "virtually no marketable skills," these are the kinds of sweet assignments she does best.
Keywords: Plum, Stephanie (Fictitious character) -- Fiction; Women bounty hunters -- Fiction; Women private investigators -- New Jersey -- Fiction; Trenton (N.J.) -- Fiction; New Jersey -- Fiction; Humorous fiction; Detective and mystery fiction